Fundamentals of wastewater treatment and engineering - Riffat, Rumana (Boca Raton : CRC Press, 2013)
'All societies depend on effective wastewater treatment and engineering, and every good civil engineer needs an understanding of the subject. This textbook presents the material necessary for a semester-long course for undergraduates and graduate students in civil and environmental engineering, and environmental technology. Each main chapter presents a topic as a theoretical section followed by example problems, and a set of questions and problems. Applicable regulations and standards are given from the World Health Organization and United States Environmental Protection Agency. Readers will get a strong grounding in the principles, and should be able to design the unit processes used in wastewater treatment operations'--
Includes bibliographical references and index.
Keywords: Sewage -- Purification